Host Genetics, Innate Immune Responses, and Cellular Death Pathways in Poliomyelitis Patients - Andersen, Nanna-Sophie B.; Larsen, Simon M.; Nissen, Sara K.; Jørgensen, Sofie E.; Mardahl, Maibritt; Christiansen, Mette; Kay, Lise; Mogensen, Trine H. (Frontiers in Microbiology, 2019)
Purpose: Poliovirus (PV) is one of the most studied viruses. Despite efforts to understand PV within the host, fundamental questions remain unanswered. These include the mechanisms determining the progression to viremia, the pathogenesis of neuronal infection, and paralysis in only a minority of patients. Because of the rare disease phenotype of paralytic poliomyelitis (PPM), we hypothesize that a genetic aetiology may contribute to the disease course and outcome. Methods: We used whole-exome sequencing (WES) to investigate the genetic profile of 18 patients with PPM. Functional analysis were performed on peripheral blood mononuclear cells (PBMCs) and monocyte-derived macrophages (MdMs). Results: We identified rare variants in host genes involved in interferon signalling, viral replication, apoptosis, and autophagy. Upon PV infection of MdMs, we observed a tendency towards increased viral burden in patients compared to controls, suggesting reduced control of PV infection. In MdMs from patients, the type I IFN response correlated with the viral burden. Conclusions: We suggest that genetic variants in innate immune defences and cell death pathways contribute to the clinical presentation of PV infection. Importantly, this study is the first to uncover the genetic profile in patients with PPM, combined with investigations of immune responses and viral burden in primary cells.